Contribution of biochar application to the promotion of circular economy in agriculture - Enaime, Ghizlane; Wichern, Marc; Lübken, Manfred (Frontiers in Agronomy, 2023)
The traditional linear model in agriculture based on the so-called ’take-make-waste’ has created many problems such as resource scarcity, waste generation, climate change and biodiversity loss. Recently, with the increase in public awareness, the attentiveness in developing a circular economy model was doubled with a focus on proper waste management to bring some benefits to the agricultural sector. Although the increasing acceptance of biochar as a carbon-based material capable of playing a multidimensional role in reducing waste, mitigating climate change, and creating a closed-loop agricultural system, it is still far to move to a final conclusion that biochar application in agriculture could bring attractive environmental and economic benefits. Research conducted so far has led to many insights into how to enhance agricultural sustainability through biochar application, as the impact of biochar is strongly interrelated to their inherent properties, which vary deeply with the nature of biomass and the preparation conditions. In the present study, a systematic literature review was performed to investigate the state- of-the-art research related to the application of biochar in agriculture and its contribution in the establishment of circular economy concept. The interlinking between biochar application in agriculture with energy-water systems and its contribution to successfully build up a circular economy model has also been investigated.